Translation of the Meaning of the Noble Qur'an karya Muhammad Taqi ud din al Hilali dan Muhammad Muhsin Khan (kajian epistemologi Tafsir) - Eed Hudaebillah (Fak. Ushuluddin, Studi Agama dan Pemikiran Islam UIN Sunan Kalijaga, 2013)
Hard1/rt